Properties of green particleboard manufactured from coconut fiber using a potato starch based adhesive - Owodunni, Amina Adedoja; Junidah, Lamaming; Rokiah, Hashim; Taiwo, Owolabi Folahan Abdulwahab; Mohd Hazwan, Hussin; Mohamad Haafiz, Mohd Kassim; Yazmin, Bustami; Othman, Sulaiman; Mohd Hazim, Mohamad Amini; Salim, Hiziroglu (NC State University, 2020)
Particleboards were manufactured using coconut fibers (Cocos nucifera). The panels were made using different green adhesives, i.e., native potato starch, citric acid, and glutardialdehyde modified potato starch, that were applied at 10%, 12%, and 15% based on oven-dry particle weight for each green adhesive type. The properties of the panels were determined according to the Japanese industrial standard. The results showed that the panels that were bonded with the 15% citric acid-modified starch green adhesive yielded the best mechanical properties (the modulus of elasticity, modulus of rupture, and internal bonding strength). The modified potato starch had potential as a green adhesive used for the production of particleboards from coconut fibers.